Coronary Artery Calcium Scoring by Cardiac CT as A Screening Tool in 40-45 Years Age Group – Predictor of Future Risk for Cardiovascular Events- Systemic Review (Nepalese Journal of Radiology, 2014)
No abstract available.DOI: http://dx.doi.org/10.3126/njr.v3i2.9604   Nepalese Journal of Radiology Vol.3(2)July-Dec, 2013: 31-36